Penyelesaian Tindak Pidana melalui Mediasi Penal di Kabupaten Pelalawan Riau dalam Perspektif Hukum Progresif dan Restorative Justice - yulianti, novi (Melayunesia Law, 2018)
Homelessness and Domestic Violence perpetrated by society are also seen as unlawful acts therefore for the perpetrators will be subject to strict sanctions. The police are trying to overcome by mediating the settlement of the case with a peaceful path but although peace is done on the normal offense the process is still carried out until it is terminated in court only that peace can be recommended as a matter of judicial consideration in deciding the case. Penal Mediation began to flourish especially after the issuance of Chief of Police Chief of Police Chief No Pol: Vol.I/No.5/Oktober-December/2013 B/3022/XII/2009/SDEOPS dated December 14, 2009, on Case Handling Through Alternative Dispute Resolution (ADR). The partial nature and the principles of penal mediation referred to in this Chief of Police emphasize that the settlement of criminal cases using the ADR, must be agreed by the litigants, but if no new agreement is settled in accordance with the applicable legal procedures professionally and proportionately.